Implementasi Analisis SWOT Dalam Strategi Pemasaran Digital Sebagai Upaya Peningkatan Siswa Baru - Vip Paramarta; Rheza Fasya; Khilda Fauziah Lasminingsih; Hanifah Sukmana; Ali Muhsin (STAI YPIQ BAUBAU, SULAWESI TENGGARA, 2024)
Implementing SWOT analysis in digital marketing strategies is crucial in increasing the number of new student registrants in educational institutions. SWOT, an abbreviation of Strengths, Weaknesses, Opportunities and Threats, provides a basis for formulating effective strategies. In the context of digital marketing, power can be utilized to strengthen an institution's image and attract the attention of prospective students through online media. Identified weaknesses can be optimized with internal improvements, thereby providing a positive experience to prospective students. Opportunities in the digital world, such as the use of social media and online platforms, can be applied to increase marketing reach. Threats from competitors can be anticipated by adapting the latest technology and increasing competitiveness. Through SWOT analysis, digital marketing strategies can be formulated to be more targeted. Strengthening an institution's image through multimedia content and testimonials can utilize internal strengths. Weaknesses such as lack of online visibility can be overcome through targeted digital marketing campaigns. Opportunities to interact directly with prospective students via social media can increase engagement. By detailing each SWOT element in a digital marketing strategy, educational institutions can increase their appeal, overcome internal obstacles, take advantage of digital opportunities, and anticipate potential threats. Thus, implementing a SWOT analysis opens up great opportunities to increase new student enrollment through a targeted and effective marketing approach in the digital era.